2018
DOI: 10.1002/mds.27484
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement disorders and neurological symptoms in late‐onset inborn errors of metabolism

Abstract: Inborn errors of metabolism in adults are still largely unexplored. Despite the fact that adult‐onset phenotypes have been known for many years, little attention is given to these disorders in neurological practice. The adult‐onset presentation differs from childhood‐onset phenotypes, often leading to considerable diagnostic delay. The identification of these patients at the earliest stage of disease is important, given that early treatment may prevent or lessen further brain damage. Neurological and psychiatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 114 publications
(217 reference statements)
0
11
0
Order By: Relevance
“…Clinical examination of eye movements is not difficult, and can be performed quickly. 8,11,12 Our results showed that the type of eye movement disorder, with a few exceptions, is often not related to a specific type of IEM. Only in NP-C and Kearns-Sayre syndrome, the observed eye movement disorders are a known characteristic of the IEM.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Clinical examination of eye movements is not difficult, and can be performed quickly. 8,11,12 Our results showed that the type of eye movement disorder, with a few exceptions, is often not related to a specific type of IEM. Only in NP-C and Kearns-Sayre syndrome, the observed eye movement disorders are a known characteristic of the IEM.…”
Section: Discussionmentioning
confidence: 62%
“…[4][5][6] Interestingly, abnormal eye movements appear to be a frequent symptom as well, but are frequently missed as physicians do not always look for them, and patients may only complain about nonspecific symptoms, such as vertigo, imbalance, and frequent falling. 7,8 Recognition of eye movement disorders in patients is important because they may serve as an additional clue in the diagnosis of an IEM. In the literature, specific patterns of ocular motor disorders are described and linked to specific types of IEMs.…”
Section: Introductionmentioning
confidence: 99%
“…Eye movement disorders are frequent in IEMs [8], but regain little attention as patients themselves do not always complain about visual disturbances. Recognition of an eye movement disorder can help to diagnose an IEM.…”
Section: Eye Movement Disordersmentioning
confidence: 99%
“…Furthermore, vertical supranuclear gaze palsy (VSGP) is a key feature. It is detected in 66 % of the patients with NP-C [4] , although this might be an underestimation as it is frequently overlooked [5] .…”
Section: Introductionmentioning
confidence: 97%